INDUSTRIAL NOISE MANAGEMENT STRATEGY BASED ON AN ENVIRONMENTAL MANAGEMENT SYSTEM IN THE GLASS PROCESSING INDUSTRY OF BEKASI CITY - Natalia Kristin; Bisti Ika Winaningsih; Bernard Hasibuan (RADJA PUBLIKA, 2026)
The development of the glass industry has the potential to increase environmental noise, which may affect the health of workers and surrounding communities. This study aims to describe the level of environmental noise at PT. ABC, a glass manufacturing company in Bekasi City, and to formulate environmental management-based noise management strategies. A descriptive research method was employed, involving direct (in situ) measurements using a Sound Level Meter at the upwind monitoring point over a 24-hour period (16–17 April 2026) in accordance with SNI 8427:2017. The gap analysis showed that noise management still needs to be strengthened, particularly in the establishment of environmental objectives, noise source mapping, and evaluation of control effectiveness. Therefore, the proposed noise management strategy refers to an Environmental Management System (EMS) based on the Plan–Do–Check–Act (PDCA) cycle, with priority given to control at the source, supported by control along the propagation path and at the receiver. This approach is expected to improve environmental performance and the operational sustainability of the industry.